Extremely fast triplet formation by charge recombination in a Nile Red/fullerene flexible dyad. Issue 33 (16th July 2021) - Faroldi, Federica; Bardi, Brunella; Tosi, Irene; Doria, Sandra; Isopi, Jacopo; Baldini, Laura; Di Donato, Mariangela; Marcaccio, Massimo; Sansone, Francesco; Terenziani, Francesca
Abstract : Fast and efficient triplet formation via charge separation followed by radical pair intersystem crossing is reported in a calixarene-based donor/acceptor dyad. Abstract : A donor/acceptor dyad was obtained by linking Nile Red and fullerene to a calix[4]arene scaffold. The dyad was spectroscopically characterized, both with steady-state and ultrafast transient absorption experiments, as well as with electrochemical and spectroelectrochemical techniques. We demonstrate extremely fast and efficient formation of a long-lived excited triplet localized on the fullerene moiety in this system, occurring in about 80 ps in toluene and 220 ps in chloroform. The mechanism of this process is investigated and discussed. The spectroscopic and electrochemical characterization suggests the occurrence of electron transfer from Nile Red to fullerene, leading to the formation of a charge-separated state. This state lives very briefly and, because of the small interaction between the electron donor and acceptor, promotes a singlet/triplet state mixing, inducing charge recombination and efficient triplet formation.